Smart sensor for EEG acquisition and epileptic seizure detection with on-chip analog classifier - Dinup Sukumaran (2013)
Epilepsy is a chronic neurological disorder affecting approximately 1% of the world’s population, which predisposes those affecting to experiencing recurrent seizures. Despite advances in currently available treatments like anti-epileptic drugs and epilepsy surgery, 25% of the patients continue to have disabling seizures. These unpredictable and medically intractable seizures make an epileptic patient susceptible to high risk of sustaining physical injuries. A reliable real-time seizure detection/prediction system that can drive an antiepileptic device or alert the patient/caregiver about the coming seizure would provide a better quality of life for epileptic patients. Our research work discusses the design of a wearable smart sensor for real-time, patient-specific epileptic seizure detection through the continuous monitoring of non-invasive EEG.